Tribological behavior of Ni–SiC composite coatings produced by circulating-solution electrodeposition technique. (July 2021) - Zhou, Y.; Sun, Z.P.; Yu, Y.; Li, L.; Song, J.L.; Xie, F.Q.; Wu, X.Q.
Abstract: Ni–SiC composite coatings were successfully deposited on interior surfaces of cylinders by circulating-solution electrodeposition (CSD) technique on a newly-designed composite electroplating apparatus. The circulating-solution agitation was effective to improve the dispersibility of SiC particles. The morphology, microstructure, hardness and tribological performances of Ni–SiC composite coatings varying SiC content were studied. Results showed that the dominant wear mechamism was oxidative wear, accompanied by abrasive wear. The friction coefficient and wear rate decreased with increasing SiC content. The excellent wear resistance was attributed to the existence of (111) growth twins, the improved hardness, the protections from NiO layer and SiC reinforcements, and the friction-induced microstructure changes underneath the tribo-surface. The protective capability of NiO layer and micro-SiC particles were discussed in detail. Highlights: Ni–SiC deposits are obtained by circulating-solution electrodeposition technique. Frictional heating promotes the formation of NiO layer at tribo-surfaces. Friction-induced deformation causes grain refinement of Ni matrix at tribo-surfaces. Interaction of SiC particles/counterbody determines the protective capability of SiC. The friction coefficient and the wear rate decrease with increasing SiC content.